Ice shelf collapse study leads to improved models.
The collapse of the Larsen B ice shelf in early 2002 was an exceptional opportunity for scientists to observe the rapid disintegration of an ice shelf of such size in real time. An EU-funded initiative used data from this event to improve models for forecasting the impact of changing ice sheets on global sea levels.